In vitro and In vivo study on the effect of Scoparia Dulcis in inhibiting the growth of urinary crystals. - Reshma Rajan; Mahima Vedi; Badrinathan Sridharan; Himaja M; Sabina E.P; N. Arunai Nambi Raj (International Journal of Phytomedicine, 2014)
Urolithiasis is a very common and highly recurring painful disease both in developing and developed nations due to the change in lifestyle and food habits. Scoparia Dulcis is herbal plant which has been used as a traditional medicine for dissolving urinary stones by the tribal group of people in Western Ghats, India. This experimental study gives a scientific awareness about the effect of Scoparia Dulcis in dissolving the urinary crystals and will confirm the drug’s effect on the organs like kidney and liver. The invitro testing was done by developing urinary crystals using single diffusion gel growth technique and the water extract of the drug is incorporated to monitor the growth of the crystal. The statistical analysis was done for the in vitro study and has proved 2ml dosage shows the highest significance in variation. In invivo testing, the urinary crystals were induced in Wistar Rats and the drug was fed to monitor its effect on the growth of crystals as well as on nearby organs. The urine and serum samples were tested for all the group of rats and parameters analysis proved the significance of the drug. The histopathology analysis gives the sectional view and report of diseased and treated groups. In both the invitro as well as invivo testing, the drug showed a significant effect in inhibiting the growth of urinary crystals.